Circular Dichroism Spectroscopy of Collagen Fibrillogenesis: A New Use for an Old Technique - Drzewiecki K.E.; Grisham D.R.; Parmar A.S.; Nanda V.; Shreiber D.I. (My University, 2025)
Type-I collagen assembles in a stepwise, hierarchic fashion from the folding of the triple helix to the assembly of fibrils into fibers. The mature assembled fibers are crucial for tissue structure and mechanics, cell interactions, and other functions in vivo. Although triple helix folding can be followed with the use of optical methods such as circular dichroism (CD) spectroscopy, fibrillogenesis is typically measured by alternative methods such as turbidity, rheology, and microscopy. Together, these approaches allow for investigation of the mechanical properties and architectures of collagen-based scaffolds and excised tissues. Herein, we demonstrate that CD spectroscopy, a technique that is used primarily to evaluate the secondary structure of proteins, can also be employed to monitor collagen fibrillogenesis. Type-I collagen suspensions demonstrated a strong, negative ellipticity band between 204 and 210 nm under conditions consistent with fibrillogenesis. Deconvolution of CD spectra before, during, and after fibrillogenesis identified a unique fibril spectrum distinct from triple helix and random coil conformations. The ability to monitor multiple states of collagen simultaneously in one experiment using one modality provides a powerful platform for studying this complex assembly process and the effects of other factors, such as collagenases, on fibrillogenesis and degradation. © 2016 Biophysical Society